2019
DOI: 10.1038/s41598-019-44965-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Colistin Administration and Bacterial and Treatment Outcomes in Critically Ill Patients

Abstract: The desired target steady-state average colistin concentration (C ss,avg ) to balance between therapeutic effectiveness and nephrotoxicity is largely unclear. The objective of this study was to evaluate the effect of the desired target colistin C ss,avg on the effectiveness and safety of IV colistin therapy in critically ill patients. Overall, 153 critically ill patients (71% males) receiving IV colistin were retrospectively analyzed. The desired target colistin C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 47 publications
3
27
4
Order By: Relevance
“…38 Earlier studies have determined that the microbiological outcome after CMS therapy is associated with highdose therapy, presence of loading dose and type/severity of underlying illness. 26,39 In our study, we did not find any predictor significantly (P < .05) associated with the microbiological outcome. As our study design was different as compared to other previous studies, we could not include patients receiving high-dose CMS therapy or loading doses of CMS to determine their influence on the microbiological outcome.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…38 Earlier studies have determined that the microbiological outcome after CMS therapy is associated with highdose therapy, presence of loading dose and type/severity of underlying illness. 26,39 In our study, we did not find any predictor significantly (P < .05) associated with the microbiological outcome. As our study design was different as compared to other previous studies, we could not include patients receiving high-dose CMS therapy or loading doses of CMS to determine their influence on the microbiological outcome.…”
Section: Discussioncontrasting
confidence: 69%
“…9,10,21,25 We observed that the APACHE II score was significantly (P < .05) associated with the clinical outcome following CMS therapy, which was consistent with the suggestions of previous reports. 26,27 None of the parameters that we tested were associated/correlated with the microbiological outcome. Also, our findings suggested that the presence or absence of ADRs due to CMS therapy was significantly (P < .05) correlated and associated with C max , AUC 0-8 , CL and V d .…”
Section: Discussionmentioning
confidence: 91%
“…Carbapenem-resistant Acinetobacter baumannii (CRAB) infections are a serious problem and increasing worldwide, particularly in the intensive care unit (ICU) [ 1 , 2 ]. The incidence of A. baumannii in ICU in Europe, Eastern Mediterranean and Africa was 56.5 cases per 1000 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of A. baumannii infection in hospital was 35.3% and of CRAB-related infection in ICU was 60.1% [ 1 ]. Due to altered physiological characteristics related to critical illness and the care provided in an ICU, such as the common use of carbapenem and invasive procedures, critically ill patients are more susceptible to CRAB infections associated with substantially increased morbidity and mortality [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation